The impact of the herd health interventions in small ruminants in low input production systems in Ethiopia - Moliso, Mesfin Mekonnen; Molla, Wassie; Arke, Asrat; Nana, Tesfalem; Ayele Zewudie, Firdawok; Tibebu, Abebe; Haile, Aynalem; Rekik, Mourad; Magnusson, Ulf; Wieland, Barbara; Knight-Jones, Theodore (Frontiers in Veterinary Science, 2024)
IntroductionDiseases have a negative impact on production and profitability of small ruminants. A good herd health program can decrease the number of sick animals and improve herd performance.MethodsIn a longitudinal study, small ruminant herd health interventions such as community-based strategic gastrointestinal (GI) parasite control, prevention and control of major respiratory diseases and capacity development activities were implemented. In four districts of Ethiopia, where the Community Based Breeding Program (CBBP) is implemented, morbidity and mortality data were collected from January 2018 to July 2021 in 1047 smallholder farms with the objective of evaluating the impact of herd health interventions. A total of 2,643 sick animals and 516 deaths of small ruminants were recorded during the study period. The disease cases were categorized into eight groups: gastrointestinal, neurological, reproductive, respiratory, skin, systemic, other diseases (eye disease, foot disease etc) and unknown diseases. Chi-square and proportions were used to analyze morbidity and mortality by district, agro-ecological zone and age of the animal.ResultsThe data showed that the general trend in the occurrence of cases and morbidity rate were decreasing from 2018 to 2021 in intervention villages. Overall, the morbidity rate in young animals (7.36%) was highier than in adults (3.49%) and the mortality rate difference between young and adult animals was also statistically significant (p < 0.001). The morbidity and mortality rates varied significantly (p < 0.001) among districts and among agro-ecologies. According to the data, treating and following up of infected animals reduced the mortality rate significantly. The relative risk of death in treated animals after the case reported was 0.135. Generally, the intervention impact analysis revealed that morbidity rate was decreased in intervention years (6.31% in 2018 to 3.02% in 2021) and that herd health interventions provide an added value.ConclusionGenerally, herd health intervention had significant impact in reducing the morbidity rates in years and treatment and follow up of sick animals due to early reporting reduced mortality rate significantly. It is recommended that the herd health management should be the core activity under small ruminant production programs.